Dynamics of Successful Formation of Professional Identity of Future Psychologists in Higher Education Institutions - Zaverukha, Olha; Popovych, Ihor; Karpenko, Yevhen; Kozmenko, Olena; Stelmakh, Oksana; Borysenko, Oksana; Hulias, Inesa; Kovalchuk, Zoriana (Lumen Publishing House, 2022)
The article is devoted to the theoretical substantiation and empirical research of dynamic features of successful professional identity’s formation of students-psychologists in institutions of higher education. The importance of this issue is substantiated and an empirical research is held. The psychological semantic features of the formation’s stages of professionalism, professional crises during the profession of psychologist at the university are studied. The influence of educational and professional activity on professional identity is outlined. The definition of professional identity as a psychological category is concretized, which is the awareness of a specialist of his belonging to a certain profession and a certain professional community. Valid psychodiagnostic tools were used and comparative and correlation analyses of data were performed. The structure of professional identity, which combines cognitive, emotional and behavioural components, is revealed. The results of empirical research confirmed that the dynamics of successful development of professional identity of future psychologists in the learning process is the gradual formation of its structural components. Crisis tendencies in the identity of third-year students have been established. They are caused by frustration in professional and life choices, inconsistency of expectations and ideas about the profession and the realities of its acquisition. The presence of identity crisis of the third-year students was established. It is proved that professional identity is determined by the conscious choice of respondents by profession. It is verified and substantiated that students, who are characterized by the formed mature professional identity, quite consciously choose the educational trajectory and carefully complete it with selective educational components.
Keywords: Identity crisis; student-psychologist; profession; educational components; educational trajectory